Marketing Strategy of “AL” Traditional Medicine Products: Case Study in “SP” Company in Yogyakarta - Putri, Felicita Eka; Ardiningtyas, Bondan; Endarti, Dwi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Exclusive breastfeeding is an effort to avoid cases of stunting in children. However, the breastmilk produced by the mother is not always enough to meet the needs of the baby. PT. SP is one of the companies that manufacture “AL” as a traditional herbal medication      (a combination of katuk and moringa leaves) that can boost milk production. However, the sales of this product are not optimal yet, meaning competent marketing strategies are needed. Objective: This study aimed to identify and analyze the internal and external factors of PT. SP to gain an understanding of the company's position so that the best marketing strategy can be determined.Methods: This study was carried out using an analytical descriptive method involving key informants including the supervisor of production, Quality Control, Quality Assurance, and the marketing division. Data analysis utilized the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE) Matrix, and Internal-External (IE) Matrix.Results: Based on the analysis PT. SP had significant internal factors for capturing opportunities and facing threats, as shown in cell IV.                      It indicated that PT. SP is a growing and developing company. The most suitable marketing strategy needed is an intensive strategy, such as market penetration, market expansion, and product development.        An integration strategy is carried out, which is forward integration.Conclusion: The company was positioned in cell IV in the IE matrix, namely growing and developing. It is suggested that the strategies that can be used to improve marketing are intensive and integration strategies.